2008
DOI: 10.1080/10410230802342150
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Use of Forceful Language When Designing Exercise Persuasive Messages for Adults: A Test of Conceptualizing Reactance Arousal as a Two-Step Process

Abstract: This investigation tests a conceptualization of reactance as a two-step process. This conceptualization was recently tested with college students, but research testing this conceptualization among primarily adult samples does not currently exist. Psychological reactance theory (PRT) states that individuals exposed to a threat or elimination of a freedom will experience reactance and subsequently be motivated to restore the freedom. Specifically, it is hypothesized that individuals will perceive persuasive mess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
164
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(179 citation statements)
references
References 30 publications
11
164
1
3
Order By: Relevance
“…Different from the effect of social agency on the psychological reactance measures, which was only found on the negative cognitions measure, the effect of threat to autonomy of the language in the advice was found both on the measure for negative cognitions and the measure for feelings of anger. This finding is in correspondence with earlier research [8,17,19,21,23] that indicates that the use of threatening language (threatening people's autonomy) and controlling language (using explicit directives) will diminish persuasion and enhance psychological reactance. Moreover, this finding was especially pronounced on the reactance measure of feelings of anger, but also present on the reactance measure of negative cognitions.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Different from the effect of social agency on the psychological reactance measures, which was only found on the negative cognitions measure, the effect of threat to autonomy of the language in the advice was found both on the measure for negative cognitions and the measure for feelings of anger. This finding is in correspondence with earlier research [8,17,19,21,23] that indicates that the use of threatening language (threatening people's autonomy) and controlling language (using explicit directives) will diminish persuasion and enhance psychological reactance. Moreover, this finding was especially pronounced on the reactance measure of feelings of anger, but also present on the reactance measure of negative cognitions.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, this finding was especially pronounced on the reactance measure of feelings of anger, but also present on the reactance measure of negative cognitions. This difference is also found in a recent other study, which also showed stronger effects related to psychological reactance on measures of anger than on measures of negative cognitions [19].…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations